How does industrial intelligence affect capacity utilization?—Analysis based on green development perspective - Yuan, Yiming; Yu, Liuming; Kumar, Sanjay; Zhang, Yi (Frontiers in Environmental Science, 2022)
This study focuses on exploring the relationship between industrial intelligence and capacity utilization based on the perspective of green development. Based on a fixed effect model, using data from the International Federation of Robotics (IFR) and China’s A-share listed enterprises from 2011 to 2019, this study empirically analyzes the influence of industrial intelligence on enterprises’ capacity utilization. The benchmark regression results reveal that industrial intelligence has a negative effect on enterprises’ capacity utilization. The results are robust to several econometric concerns. Moreover, mechanism analysis indicates that industrial intelligence affects enterprises’ capacity utilization through the productivity effect, the green innovation effect, and the scale expansion effect. When considering the heterogeneity at regional levels, we find that enterprises in the central and western regions are more affected by industrial intelligence. Our findings provide guidance to enterprises and policymakers in addressing industrial overcapacity and green development issues in China.